Nurses are underutilised in antimicrobial stewardship – Results of a multisite survey in paediatric and adult hospitals - Mostaghim, M.; Snelling, Thomas; McMullan, B.; Konecny, P.; Bond, S.; Adhikari, S.; Chubaty, A.; Lovell, C.; Bajorek, B. (2017)
© 2017 Australasian College for Infection Prevention and Control Objectives Explore perceptions and attitudes of nurses in regard to antimicrobial stewardship (AMS), their roles as nurses, and identify differences in perceptions and attitudes across paediatric and adult settings. Methods Electronic survey administered to nursing staff across three public Australian tertiary institutions with AMS facilitated by a shared electronic approval and decision support system. Results Overall 65% (93/142) of nurses who completed the survey were familiar with the term AMS, and 75% recognised that they were expected to have a role alongside other disciplines, including ward pharmacists (paediatric 88%, adult 73%; p = 0.03). Hand hygiene and infection control (86%), patient advocacy (85%) and knowledge of antimicrobials (84%) were identified most often as AMS roles for nurses. However, 57% of nurses reported that their knowledge of antimicrobials was minimal or limited. Nurses generally agreed that requirement to obtain approval is an effective way to reduce inappropriate antimicrobial use (median scores: paediatric 2.0 [agree], adult 1.0 [strongly agree] ; p = 0.001). Only 35% of paediatric and 58% of adult nurses perceived that their role includes ensuring approval for restricted antimicrobials (p < 0.01). Most nurses identified AMS teams (85%), pharmacists (83%) and infection control teams (paediatric 68%, adult 84%; p = 0.04) as sources of AMS support. Areas of interest for support and education included appropriate antimicrobial selection (73%) and intravenous to oral antimicrobial switch (paediatric 65%, adult 81%, p = 0.03). Conclusion Nurses consider AMS activities within their roles, but are underutilised in AMS programs. Further engagement, education, support and acknowledgement are required to improve nursing participation.